2012
DOI: 10.1128/jvi.06361-11
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Export and Expression of Human T-Cell Leukemia Virus Type 1 tax / rex mRNA Are RxRE/Rex Dependent

Abstract: Human T-cell leukemia virus type 1 (HTLV-1) is a complex retrovirus associated with the lymphoproliferative disease adult Tcell leukemia/lymphoma (ATL) and the neurodegenerative disorder tropical spastic paraparesis/HTLV-1-associated myelopathy (TSP/HAM). Replication of HTLV-1 is under the control of two major trans-acting proteins, Tax and Rex. Previous studies suggested that Tax activates transcription from the viral long terminal repeat (LTR) through recruitment of cellular CREB and transcriptional coactiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 36 publications
0
24
1
1
Order By: Relevance
“…Why HIV-1 exploits the CRM1 pathway as opposed to the NXF1/NXT pathway that mediates the bulk of cellular mRNA nuclear export is unknown. However, Rev and Rev-equivalent proteins found in other retroviruses clearly provide a sophisticated feedback mechanism for tight regulation of late viral gene expression, with possible roles in viral persistence and immune evasion (11)(12)(13)(14). Moreover, Rev may govern the efficiency of downstream cytoplasmic events, including Gag/GagPol translation (15), gRNA packaging (16), and virus particle assembly occurring at the plasma membrane (17,18), through regulating the composition of distinct Rev/mRNA viral ribonucleoprotein (vRNP) complexes (19,20).…”
mentioning
confidence: 99%
“…Why HIV-1 exploits the CRM1 pathway as opposed to the NXF1/NXT pathway that mediates the bulk of cellular mRNA nuclear export is unknown. However, Rev and Rev-equivalent proteins found in other retroviruses clearly provide a sophisticated feedback mechanism for tight regulation of late viral gene expression, with possible roles in viral persistence and immune evasion (11)(12)(13)(14). Moreover, Rev may govern the efficiency of downstream cytoplasmic events, including Gag/GagPol translation (15), gRNA packaging (16), and virus particle assembly occurring at the plasma membrane (17,18), through regulating the composition of distinct Rev/mRNA viral ribonucleoprotein (vRNP) complexes (19,20).…”
mentioning
confidence: 99%
“…However, studies based on expression of intronless mature mRNAs showed that expression of tax/rex, as well as other viral transcripts, may be enhanced by Rex through a canonical RXRE-and CRM1-dependent pathway (42,43). In fact, Rex is capable of binding tax/rex mRNA in chronically infected cell lines (43).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies based on expression of intronless mature mRNAs showed that expression of tax/rex, as well as other viral transcripts, may be enhanced by Rex through a canonical RXRE-and CRM1-dependent pathway (42,43). In fact, Rex is capable of binding tax/rex mRNA in chronically infected cell lines (43). The distinct observations made from a study of full-length proviruses versus mRNAs produced from cDNA expression plasmids indicate that the latter may be subjected to additional expression constraints that are not encountered by transcripts that interact with the splicing machinery.…”
Section: Discussionmentioning
confidence: 99%
“…p30 also regulates the cell cycle and the DNA damage response and is important for viral persistence in vivo (Anupam et al, 2013). ORF III encodes Rex which binds to the Rex response element on unspliced and singly spliced viral RNAs and shuttles these RNAs from the nucleus to the cytoplasm for translation by the host machinery (Bai et al, 2012). Tax is encoded by ORF IV and is essential for transactivation of viral gene expression by recruiting host transcription factors CREB and AP-1 and coactivators CBP/p300 to the LTR (Harrod et al, 1998).…”
Section: Human T-cell Leukemia Virus Type 1 (Htlv-1)mentioning
confidence: 99%